Slow-Freezing Cryopreservation of Gonadal Tissue Prior to Anti-Cancer Therapy for Fertility Preservation - Lieonova, Olena Yu.; Bogdaniuk, Anastasiia O. (Problems of Cryobiology and Cryomedicine, 2018)
Â Probl Cryobiol Cryomed 2018; 28(2): 167